IMPLEMENTATION OF THE UMMI METHOD OF QURAN RECITATION FOR INCLUSIVE LOW-CLASS ELEMENTARY SCHOOL STUDENTS AT SD MUHAMMADIYAH KREMBUNG - Rezania, Vanda; Aruni Lathifah, Vina (Journal of Higher Education and Academic Advancement, 2025)
Objective: The UMMI method aims to enhance Quranic learning, particularly focusing on improving reading fluency and adherence to tartir principles. This method integrates musical elements and voice modulation to facilitate Quranic memorization and recitation. Additionally, it addresses the specific needs of inclusive education settings, tailoring the approach to the diverse abilities and characteristics of students with special needs. Methods: The study employed a tailored pedagogical approach that incorporates the UMMI method into inclusive classrooms. The method combined individualized and cooperative strategies to address the needs of children with special requirements. Individualized strategies were used to customize learning experiences based on each student's abilities, while cooperative strategies encouraged collaboration between students with special needs and their peers. Results: The findings indicate that the UMMI method effectively supports Quranic learning for students with special needs in inclusive education settings. Individualized approaches ensured that every student could access Quranic education that matched their unique needs. Cooperative strategies further fostered interaction and collaboration, enabling inclusive participation in Quranic learning. These combined approaches helped students develop their Quranic reading skills and encouraged equitable access to educational opportunities. Novelty: This study highlights the innovative application of the UMMI method in inclusive education, demonstrating its adaptability to diverse learning environments. By integrating individualized and cooperative strategies, the method bridges the gap in Quranic education for students with special needs, offering a unique blend of pedagogical techniques that cater to inclusivity and individual growth.